Pengaruh Bahan Ajar Muatan Lokal Konservasi Flora Khas Bengkulu Terhadap Sikap Peduli Lingkungan Siswa Kelas V Sekolah Dasar Di Kota Bengkulu - Endang Widi Winarni; Wurdjinem Wurdjinem; Selfika Lestari (Universitas Bengkulu, 2018)
The purpose of this research is to know the influence of local content teaching material of Bengkulu flora conservation to the environmental caring attitude of grade V elementary school students in Bengkulu city. This type of research is a quantitative research with the design of The Matching Only Pretest-Posttest Control Group Design. The sample in this research is VC students of SD Negeri 19 Bengkulu as an eskperimen class and students of VD SD Negeri 74 Bengkulu as control class. The instrument used in this research is a questionnaire of environmental care attitude using Likert scale. Data of this research are analyzed by using inferential analysis that is t-pooled variance test. The result of inferential analysis using t-test shows that thitung (3.954) is bigger than ttable (2,000), so it can be concluded that there is significant effect of local content material of Bengkulu flora conservation on environmental caring attitude of grade V elementary school student in Bengkulu city.